2018
DOI: 10.3389/fpls.2018.01562
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Cassava Root Starch Phosphorylation Enhances Starch Functional Properties

Abstract: Cassava (Manihot esculenta Crantz) is a root crop used as a foodstuff and as a starch source in industry. Starch functional properties are influenced by many structural features including the relative amounts of the two glucan polymers amylopectin and amylose, the branched structure of amylopectin, starch granule size and the presence of covalent modifications. Starch phosphorylation, where phosphates are linked either to the C3 or C6 carbon atoms of amylopectin glucosyl residues, is a naturally occurring modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Interestingly, this frequently alters other structural features of starch besides its phosphate content. It has been reported that starch functional properties are influenced by many structural features, including relative amounts of two glucan polymers, amylopectin and amylose; the branched structure of amylopectin; the starch granule size; and the presence of covalent modifications . de Graaf et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this frequently alters other structural features of starch besides its phosphate content. It has been reported that starch functional properties are influenced by many structural features, including relative amounts of two glucan polymers, amylopectin and amylose; the branched structure of amylopectin; the starch granule size; and the presence of covalent modifications . de Graaf et al.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic background was not a limiting factor to ethanol yield, but specific genes involved in important phonotype should have more effect to the traits related to phosphorylation in which the semi‐crystalline packing of amylopectin is disrupted, making the glucan chains at the granule surface more accessible to glucan‐degrading enzymes such as amylases, and enhancing the ethanol yield based on starch dry matter. Starch phosphorylation in the storage root of cassava is reported to be related to endogenous phosphoglucan phosphatase genes such as MeSEX4 and MeLSF2 . Another possible alteration of different genotypes among cultivars that influence starch degradation using alpha‐amylase and glucoamylase is the gene related to the lack of amylose in waxy genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Cassava ( Manihot esculenta Crantz) is one of the most important starchy crops worldwide, providing staple food for more than 700 million people in the tropics and subtropics (Hershey 2017). Compared with other starches (e.g., from maize and potato), pure‐white cassava starch contains low levels of fat (0.08%–1.54%) and proteins (0.03%–0.6%); less phosphorylation of the glucose moieties has also been reported in cassava starches (Blennow et al 2001; Wang et al 2018). These features make cassava an excellent starch resource for various industrial applications (Richard et al 1991; Balagopalan 2002; Moorthy 2002; Sharma et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Sweet potato starch is particularly valued as an important ingredient in the manufacturing of starchbased food products, such as noodles, vermicelli, jellies, steamed bread, cakes, alcoholic beverages, soup, flavoring agents, sweeteners, and other consumables [61]. Sweet potato starch is suitable for producing resistant starch, which helps to reduce the postprandial blood glucose level and reduces the risk of obesity and diabetes [101]. Resistant starch is considered to be an important value-added starch product with increasing market demand.…”
Section: Value-added Products From Sweet Potato Starchmentioning
confidence: 99%